Influence of postoperative alignment on clinical outcome following medial open-wedge osteotomy for medial gonarthrosis in patients with underlying varus deformity. Issue 4 (27th April 2017) - Hohloch, Lisa; Mehl, Julian; Niemeyer, Philipp; Südkamp, Norbert; Bode, Gerrit
Aims and Objectives: High tibial osteotomy (HTO) has gained more and more importance in the treatment of cartilage damage of the medial compartment with concurrent varus deformity. Concerning the extent of axis correction, various different views exist. The aim of this study was to evaluate the effect of the degree of axis correction on the functional outcome in patients suffering from cartilage damage of the medial compartment and undergoing a valgus HTO. Materials and Methods: From January 2005 to December 2013 there were 156 patients suffering from cartilage damage of the medial compartment and an underlying varus deformity who were treated by a biplanar valgus HTO. According to the degree of axis correction - mirrored by the position of the intersection point of the weight bearing line and the tibial plateau - patients were allocated to different groups. For this purpose 3 adjacent areas respectively comprising 5% of the tibial plateau were defined. Limits of those areas were set as follows: with the medial border representing the 0%-point and the lateral border representing the 100%-point, the 3 areas were separated according to their intersection point (group 1 50-55%, group 2 55-60%, group 3 > 60%). For comparison of the functional outcomes, standardized measures and scores were used (pre-OP: VAS, Lysholm; post-OP: VAS, Lysholm, KOOS, IKDC). Analysis of the pre- and post-operatively recorded X-Rays was effected by means of a planning software (mediCAD Hectec GmbH, Germany), statistical analysis was carried out with the aid of SPSS Statistics 21.0 (IBM Corp., Armonk, USA.). A p-value of 0.05 was considered statistically significant. Results: 39 patients were allocated to group 1, 49 patients to group 2, 68 to group 3. Concerning mean follow up, age, gender, height, weight and pre-operative VAS there were no statistically significant differences (p>0, 05). Thus, patients in each group were of a homogenous constitution. Regarding outcome parameters, group 1 showed significantly higher results. They reached statistical significance when comparing results of the Lysholm score (83, 50±15, 41 vs. 68, 64±23, 31 vs. 61, 36±30, 58), KOOSpain (89, 93±9, 62 vs. 77, 15±15, 37 vs. 74, 24±21, 05), KOOS (81, 25±9, 20 vs. 72, 63±17, 38 vs. 66, 45± 19, 29), KOOS4 (77, 89±10, 69 vs. 69, 56±18, 21 vs. 63, 28±19, 35) and VAS post-OP (1, 88±1, 73 vs. 2, 36±0, 92 vs. 3, 45±2, 84). A positive correlation between height and KOOSpain (Pearson correlation 0, 181) KOOSadl (PC 0, 239), KOOSsport (PC 0, 213) and KOOS5 (0, 196)was calculated . A negative correlation existed between age and Lysholm Post (PC -0, 207), KOOSpain (PC 0, 190), KOOSadl (PC -0, 231) and KOOSges (PC -0, 161) Conclusion: Valgus HTO of varus deformity in patients with concomitant cartilage damage of the medial compartment is highly efficient regarding functional outcome. Precise preoperative planning regarding individual factors in each patient is mandatory as correction to a neutral weight bearing axis or only mild overcorrection seem to be beneficial in comparison to larger correction angles.